Biodiversity patterns of cavernicolous ground-beetles and their conservation status in the Azores, with the description of a new species: Trechus isabelae n. sp (Coleoptera : Carabidae : Trechinae) - Borges, Paulo A. V. (2007)
Diversity patterns of cave and epigean Trechinae (Coleoptera, Carabidae) from the Azores (Portugal) are reported based on recently standardized sampling protocols in different habitats of this geologically young and isolated volcanic archipelago. A total of 10 species are studied, including Trechus isabelae n. sp., collected in a volcanic pit on São Jorge, one of the nine islands of the Azores. This new Trechus species represents the eighth species of Trechinae described from the underground environment of the Azores. An identification key for the Azorean species of Trechus is provided along with additional information per species on their distribution and conservation status in the archipelago. Possible reasons for the different degrees of adaptation to the conditions of the underground environment exhibited by Trechinae are also discussed.